Interaksi Sosial Anak Down syndrome di Panti Asuhan SLB-C Santa Lusia Kota Medan - Juita Anriani Simaremare; Wira Fimansyah (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This research aims to describe the social interaction patterns of children with Down syndrome at the SLB-C Santa Lusia Orphanage, determine the perceptions of teachers and nurses regarding the social interactions of children with Down syndrome, and determine the impact of social interaction on the social, emotional and cognitive development of children with Down syndrome. syndrome at the SLB-C Santa Lusia orphanage. The research method used in this research is a qualitative method with a descriptive approach. This research was conducted at the SLB-C Santa Lusia Orphanage, Medan City. The data collection techniques used were interviews, documentation and observation. The results of this research are that the social interactions of children with Down syndrome can be formed in three main patterns that influence their development, namely predation, symbiosis and competition. The support provided by teachers and nurses is essential in helping children identify and express their feelings healthily. For example, when children feel happy, proud, or even disappointed, teachers and nurses play a role in helping them manage these feelings in a way that is consistent with social norms, teaching them how to express emotions positively, and strengthening emotional relationships with other people. The impact of positive social interactions is clearly visible in the social, emotional and cognitive development of children with Down syndrome. Involvement in group activities such as making soap, making chips from sweet potatoes, and also dancing can create a sense of togetherness that reduces feelings of isolation and increases feelings of acceptance.